A Study of Flood Causal Priority in Arui Watershed, Manokwari Regency, Indonesia - Mahmud Mahmud; Ambar Kusumandari; Sudarmadji Sudarmadji; Nunuk Supriyatno (Institut Pertanian Bogor (IPB University), 2018)
Papua is the final fortress of forests in Indonesia. However, floods recently occurred in Jayapura, Paniai, and Manokwari. If causal factors are not identified and early anticipated, the flood will become an annual disaster with more severe impacts. This study aims to identify main factors causing floods using scoring analysis. Data collected include: rainfall, river gradient, water discharge, drainage density, watershed shape, slope and land use. The research results show that the main factor of floods are average daily rainfall in wet month by 86.53 mm day-1 (rather high) with a score of 28, land use dominated by forest and plantation (rather low and medium) with a score of 21, watershed slope dominated by 1-<8% (high) with a score of 5, drainage density of 6.4 (medium) with a score of 3, watershed shape (Rc of 0.30 < Re 0.71) with somewhat/elongated shape with a score of 2, and river gradient of 0.0062 (low) with a score of 2 respectively. High rainfall causes greater flow of water and runoff. Land use dominated by plantations (21.46%) is thought to be one of the main causes of floods in Masni District. Flood mitigation does not mean that rain should be reduced, but regulates/manages such as stopping the conversion of forest into palm oil plantations, reducing surface runoff by applying soil conservation, making bypass from meandering, dredging sediments, and constructing retaining walls.